Analisis Norma Sosial Dalam Cerpen “Selamat Pagi, Penganggur!” Karya Seno Gumira Ajidarma Dengan Menggunakan Pendekatan Sosiologi Sastra - Meta Agesta Kalih Purwasih; Dio Armando (Jurnal Pendidikan dan Kewarganegara Indonesia, 2024)
This study examines social norms in the short story "Good Morning, Unemployed!" by Seno Gumira Ajidarma using a literary sociology approach. This work describes the dynamics of the life of an unemployed person who is often the target of community stigma. Social norms, such as the pressure to be economically independent and the hope of success, are examined through the narratives and characters in this short story. The study reveals the psychological impact of stigma, unfair access to opportunities, and the importance of solidarity amid social pressure. This analysis shows the role of short stories as a medium of reflection and criticism of social reality that is often overlooked. With a qualitative descriptive approach, this study emphasizes the relevance of social issues in literature as a reflection and driver of public awareness.